MHD free convection boundary layer flow near the lower stagnation point flow of a horizontal circular cylinder in ferrofluid - Siti Hanani, Mat Yasin; Muhammad Khairul Anuar, Mohamed; Zulkhibri, Ismail; Mohd Zuki, Salleh (IOP Publishing, 2020)
The present numerical solution is to theoretically investigate the magnetohydrodynamic (MHD) free convection boundary layer flow and the heat transfer of ferrofluid near the lower stagnation point of a horizontal circular cylinder. The conventional heat transfer of fluids such as water and oil is inherently the poor heat transfer performance. Nanofluid which is formed by magnetic nanoparticles is known as ferrofluid and has shown a particular achievement when the effect of external magnetic is applied. For this purpose, ferrofluid that contains magnetite, Fe3O4 and water are considered. The dimensional governing equations are transformed by using non-dimensional variables and non-similar transformations to form nonlinear partial differential equations. The numerical solution using the implicit finite difference scheme namely Keller-box method is used to solve the nonlinear partial differential equations. Numerical results on velocity and temperature distributions as well as the quantity of interest of pertinent parameters such as magnetic parameter and the volume fraction of ferroparticles parameter are discussed. It is noticeable that the reduced Nusselt number of ferrofluid decreases through the increase of magnetic parameter strength.